Kandungan Bilangan Peroksida Minyak Goreng Pedagang di Jalan Perintis Kemerdekaan Kota Padang - Intan Permata Sari Syafrudin; Asterina Asterina; Russilawati Russilawati (Fakultas Kedokteran, Universitas Andalas, 2021)
Background. Indonesian usually using repeatedly cooking oil for deep frying process. The repeated use of cooking oil can be found among street vendors. Consumption of repeatedly cooking oil could lead to hepatic disorder, cardiovasular disorder and even cancer. Objective. The research aims to describe and analyze peroxide value in cooking oil used by street vendors in Perintis Kemerdekaan street in Padang City. Methods. This is a descriptive research. The reseacrh objects were taken by purposive sample method and 23 samples cooking oil used by traders. This research was conducted at Clinical Laboratory of West Sumatera from October 2019 to May 2020. Results. This research found out 14 from 23 of cooking oil used by street vendors have peroxide value above the Indonesian National Standard (abbreviated SNI) 01-3741-2013. Cooking oil used by fritter street vendors have average peroxide value is 15.10 mEq O2/kg while pecel catfish and chicken street vendors is 10.29 mEq O2/kg. The avarage peroxide value in each type of cooking oil are bulk 10,81 mEq O2/kg, branded 14,64 mEq O2/kg and mixture 16,28 mEq O2/kg. Conclusion. More than half of the samples tested had exceed the maximum peroxide values (> 10 mEq O2/kg) and the highest average are found in fritter street vendor and mixture of bulk and branded cooking oil.